MENGUNGKAP TREN PEMBAYARAN QRIS TERPOPULER DAN DINAMIKA PERILAKU PENGGUNA DI SALAH SATU PTN VOKASI BANDUNG - Rosliana, Joy Tessyaloni; Azzahra, Alifia Aura (Media Mahardhika, 2025)
Digital payments continue to grow over time, especially payment through the QRIS (Quick Response Code Indonesian Standard) method has become a digital payment innovation that is growing ubiquity in all circles, especially among students. The purpose of this study is to determine usage trends of QRIS at Politeknik Negeri Bandung, banks, and students' favorite digital wallets, and identify related factors that influence the choice of payment methods. The research method used a quantitative approach, the data was collected through a questionnaire involving 102 respondents from various departments throughout Politeknik Negeri Bandung and then the data was processed with the aid of SPSS 23. The outcomes of the analysis explained that BRI bank was the most popular bank with a percentage of 39.2% and DANA digital wallet was the most popular choice among Politeknik Negeri Bandung students. In addition, QRIS has been shown to significantly impact user behavior, using the coefficient of determination (r²) value of 67%. The convenience, security, and customization factors of QRIS contribute to its widespread adoption in the Bandung State Polytechnic campus environment. This research aims to be a reference for educational institutions and financial service providers in optimizing a better and more suitable digital payment system, especially among students.